Artificial Intelligence in the Power Sector - Makala, Baloko (International Finance Corporation, Washington, DC, 2020)
The energy sector worldwide faces growing challenges related to rising demand, efficiency, changing supply and demand patterns, and a lack of analytics needed for optimal management. These challenges are more acute in emerging market nations. Efficiency issues are particularly problematic, as the prevalence of informal connections to the power grid means a large amount of power is neither measured nor billed, resulting in losses as well as greater CO2 emissions, as consumers have little incentive to rationally use energy they don’t pay for. The power sector in developed nations has already begun to use artificial intelligence and related technologies that allow for communication between smart grids, smart meters, and Internet of Things devices. These technologies can help improve power management, efficiency, and transparency, and increase the use of renewable energy sources.